KatG, the bifunctional catalase of xanthomonas citri subsp. citri, responds to hydrogen peroxide and contributes to epiphytic survival on citrus leaves - Tondo, María Laura (2016)
Fil: Fil: Tondo, María Laura. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR -CONICET); Argentina.